The Use of Authentic Material in English Classroom Teaching: Indonesian New Curriculum - Hariri, Alfan; Ficayuma, Lina Aris (IJET (Indonesian Journal of English Teaching), 2023)
The Indonesian current curriculum is derived as operational curriculum for school initiator (KOSP). In language learning, the KOSP focuses on the competences to use the language with six basic skills: listening, reading, speaking and writing, with addition Watching and presenting. “watching and presenting” skills is to accommodate the receptive skill from the video and productive skill through media content such as YouTube, Instagram, Tik Tok etc. The KOSP uses genre-based approach in language teaching that emphasizes on the contextual applicable use of the language. with four main activities: Building knowledge of the text, Modelling of the text, Joint construction of the text and Independent construction of the text. In addition, this paper explores about the use of authentic material and its advantages in language learning classroom. Furthermore, the paper presented some example about the use of authentic material in implementing KOSP specifically for basic English in Junior and senior high school. The first authentic material is students’ photograph to teach recount text where the students tell about the photograph either in written and oral. The second authentic material is students’ realia to teach descriptive text.